Development of a Marker-Based Augmented Reality Application for Computer Hardware Learning Using the Multimedia Development Life Cycle - Muhamad Adila Syahputra; Ade Syahputra; Silvester Dian Handy Permana (JISA(Jurnal Informatika dan Sains), 2026)
Understanding computer hardware is a fundamental competency for vocational students. However, limited access to physical hardware components often restricts practical learning activities in vocatioal schools. This study aims to develop and evaluate VirtuComp, a marker-based Augmented Reality (AR) application for computer hardware learning using the Multimedia Development Life Cycle (MDLC) methodology. The application visualizes seven essential computer hardware components as interactive three-dimensional (3D) objects to support students in recognizing and understanding hardware structures through an immersive learning experience. The development process followed the six phases of the MDLC framework. The application was evaluated through functional performance testing and usability assessment involving 68 tenth-grade students from SMK Muhammadiyah 02 Cileungsi using the User Experience Questionnaire (UEQ). The functional evaluation demonstrated that the marker-based tracking system operated reliably under adequate lighting conditions with an optimal detection distance of 4–12 cm. The usability evaluation produced positive results across all six UEQ dimensions. Efficiency achieved a score of 1.89, which was classified as Excellent. Attractiveness (1.74), Perspicuity (1.78), and Stimulation (1.38) were rated as Good, while Dependability (1.40) and Novelty (0.96) were categorized as Above Average. These findings indicate that the proposed application provides a reliable and user-friendly learning medium that supports computer hardware education, particularly in vocational schools with limited laboratory resources.